Cellulose‐based hydrogels for personal care products. (28th May 2018) - Bashari, Azadeh; Rouhani Shirvan, Anahita; Shakeri, Mina
Abstract : Name of cellulose is referred to a type of natural carbohydrate with many hydroxyl groups and high water absorption capacity. Cellulose is the most abundant natural polymer, found as the main constituent of plants (plant cellulose). Some bacteria such as Acetobacter xylinum are also able to synthesize bacterial cellulose. Cellulose‐based hydrogels are superabsorbent materials, which make 3D networks. Chemical bonds or other cohesive forces such as hydrogen bonding or ionic interactions connect the cellulose chains together. Hydrogels can swell and absorb water and other aqueous fluids in their 3D networks, but they are insoluble in them. Nowadays, an increasing demand emerges for biodegradable materials and products made from renewable resources such as cellulose. The excellent biocompatibility of cellulose has prompted the large use of cellulose‐based personal care products. Cellulose hydrogel is used for these products as the thickener and stabilizing agents or as moisturizing agent to improve the skin feel of the product. Hygienic cellulosic absorbent products such as diapers, panty liners, tampons, paper towels, and tissue papers are used as personal care products. These products are available in different absorbency ratings from junior to ultra‐absorbency. Using cellulose‐based hydrogel, superabsorbent products are made. In this review, applications of cellulose‐based hydrogels in personal care products were reviewed.